Direct Contact Ultrasound in Food Processing: Impact on Food Quality - Astráin-Redín, Leire; Alejandre, Marta; Raso, Javier; Cebrián, Guillermo; Álvarez, Ignacio (Frontiers in Nutrition, 2021)
Consumers’ demand for “minimally processed” products that maintain the “fresh-like” characteristics has increased in recent years. Ultrasound (US) is a non-thermal technology that enhances mass and energy transfer processes resulting in improved food quality. A new method of applying US to food without using a liquid or gaseous medium for the propagation of acoustic waves has recently been under research. It is known as direct contact US, since the food is directly placed on a plate where the transducers are located. In this type of systems, the main effect is not cavitation but acoustic vibration, which encourages mass and energy transfer processes due to the “sponge effect”. Furthermore, as the product is not immersed in a liquid medium, the loss of hydrophilic nutritional compounds is reduced; systems such as these can thus be more easily implemented on an industrial level. Nevertheless, the very few studies that have been published about these systems mainly focus on dehydration and freezing. This article summarizes published research on the impact of direct contact US in nutritional.